Dried distiller's grains with solubles ability to replace soybean meal in Boer goat diets - Gilliam, Gabryelle N.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Currently there is little data available to producers regarding basic nutrition for growing Boer goat kids. Feed costs are often the greatest expenses associated with raising livestock, so finding ways to make the goats more efficient in terms of growth without sacrificing carcass performance should be a main focus for the industry. Therefore, the objective of this trial was to evaluate the efficacy of replacing soybean meal (SBM) with dried distiller’s grains with solubles (DDGS) in a growing Boer goat diet with regards to growth and carcass responses. The experiment consisted of four different treatments with varying inclusion rates of DDGS (0%, 33%, 66% and 100%). Prior to starting the trial, the goats were involved in a DDGS step-up program. Our trial consisted of 48 Boer goat kids, roughly 70 days of age, weighing between 28.2-28.4 kg on day 0. Each treatment consisted of 4 pens with 3 goats per pen in a completely randomized design. Goats were fed for 47 days with both the goats and feeders being weighed weekly to determine ADG, ADFI, and G:F. Following the trial, 2 goats per pen were slaughtered at a USDA inspected facility to analyze HCW, LEA, back fat depth, and body wall thickness. Data was analyzed utilizing the GLIMMIX procedure (SAS 9.4, Cary, NC) with an alpha value of 0.05. Upon analysis of the data, it was found that G:F was the only factor that showed a significant difference (P<0.001) with the increased levels of DDGS. There was a significant difference (P<0.032) in inclusion of 100% DDGS versus 0% in ADG, but no significant differences (P>0.05) were seen in the carcass traits, ADFI, or ending body weight. HCW did increase from 18.4 to 19.8 kg across the treatments, which makes further research to explore carcass performance necessary. Therefore, this experiment concluded that DDGS can effectively replace SBM up to 100% with improved G:F and ADG, and have no negative impacts on carcass performance. Replacing 100% of SBM with DDGS could save the producer up to $53.19/ton. These combined results make replacing SBM with DDGS an economically smart decision for the Boer goat producer.
Keywords: Spring 2018